Hubungan Dukungan Sosial Teman Sebaya dengan Kesiapan Kerja pada Siswa di SMK X - Istiqomah, Divya (Arus Jurnal Pendidikan, 2024)
Peers with work readiness in students at SMK X. The work readiness variable is measured using the scale "The Work Readiness Scale (WRS) developed by Caballero, et.al (2011) is made based on aspects of work readiness, namely personal characteristics or personal characteristics, organizational acumen or organizational acumen, work competence or work competence, and social intelligence or social intelligence. and peer social support is measured using the peer social support scale compiled by Zimet (1998) made based on aspects of peer social support put forward by Zimet (1998) namely family support, friend support and support from special people. This study involved 134 students of SMK X using saturated sampling techniques, then data analysis was carried out using simple linear regression using the help of the SPSS application version 20.0 for Windows. The results of the study showed that there was a positive and significant relationship between peer social support and work readiness of SMK X students. The effective contribution between the peer social support variable and work readiness was 27.3% to work readiness